Interventions to enhance psychological resilience in forcibly displaced children: a systematic review - Aya Thabet; Sonia Ghandi; Erin K Barker; Geroge Rutherford; Mohsen Malekinejad (BMJ Global Health, 2023)
Background Children represent nearly 40% of forcibly displaced populations and are subject to stressors that affect well-being. Little is known about the effects of interventions to enhance psychological resilience in these children, outside clinical settings.Methods We conducted a systematic review, following Cochrane methods. Eligible studies tested resilience-enhancing interventions outside clinical settings in forcibly displaced children/adolescents. We included longitudinal quantitative studies with comparator conditions irrespective of geographical scope or language. We searched articles published between January 2010 and April 2020 in PubMed, Embase, Cochrane Library, Web of Science, PsycINFO and the WHO’s Global Index Medicus. To standardise effect sizes across the different reported outcomes, we transformed reported mean differences to standardised mean differences using Hedge’s g statistic with associated 95% CI. We pooled data for meta-analysis where appropriate. We used Cochrane tools to assess study risk of bias and used Grading of Recommendations Assessment, Development and Evaluation to determine evidence quality for meta-analysed outcomes.Results Searches yielded 4829 results. Twenty-three studies met inclusion criteria. Studies reported 18 outcomes measured by 48 different scales; only 1 study explicitly measured resilience. Eight studies were randomised controlled trials; the rest were non-randomised pre–post studies. Interventions were diverse and typically implemented in group settings. Studies reported significant improvement in outcomes pertinent to behavioural problems, coping mechanisms and general well-being but not to caregiver support or psychiatric symptoms. In meta-analysis, resilience was improved (gav=0.194, 95% CI 0.018 to 0.369), but anxiety symptoms and quality of life were not (gav=−0.326, 95% CI −0.782 to 0.131 and gav=0.325, 95% CI −0.027 to 0.678, respectively). Risk of bias varied. Quality of evidence for most graded outcomes was very low.Conclusions The multiplicity of study designs, intervention types, outcomes and measures incumbered quantifying intervention effectiveness. Future resilience research in this population should use rigorous methods and follow reporting guidelines.PROSPERO registration number CRD42020177069.